Pembuatan Biodiesel Berbahan Baku CPO Menggunakan Reaktor Sentrifugal dengan Variasi Rasio Umpan dan Komposisi Katalis - Ardago Lengga Muda Siregar; Idral Idral; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
One  of many  sources  of  alternative  fuel  is  biodiesel  . Biodiesel  production  cost  is  still quite  expensive,  it  need  a  technology  to  reduce  thecost  of  biodiesel  production  .  Centrifugal reactor  technology  is  one  of  the  alternative  technology  of  biodiesel  production, which  is  very likely to be developed .Study of biodiesel production using palm oil as the feedstock, methanol as the  reagent, and NaOH as catalyst.This  research use centrifugal  reactor as  the  reactor, which has  a  pre-heater  for  feed,  feed  tank  and  pumps.  The  study  was  conducted  at  the  reaction temperature of 60ºC with a residence time in the reactor for 2 hours . CPO mixture , methanol , and a catalyst in the feed the reactor with variation in the molar methanol : CPO ( 3:1 , 6:1 , 9:1 , 12:1  ) and  the variation of  the  composition of  the catalyst  ( 0.5, 0.75, 1 %  - w  )  . From  the results of the study showed that the molar ratio and catalyst composition affects the speed of the reaction  to reach equilibrium reaction  . The results showed biodiesel using centrifugal reactor reaches  a  yield  of  92.6 %  under  the  conditions  of  9:1  molar  ratio  with  0.75 %-w  catalyst  . Characteristics of biodiesel produced in the form of viscosity , density , acid number , and flash point of biodiesel are qualified as Indonesian standards of Biodiesel.